The Presence of Mutations in the K-RAS Gene Does Not Affect Survival after Resection of Pulmonary Metastases from Colorectal Cancer. (4th February 2014) - Zabaleta, Jon; Aguinagalde, Borja; Izquierdo, José M.; Bazterargui, Nerea; Laguna, Stephany M.; Martin-Arruti, Maialen; Lobo, Carmen; Emparanza, José I.
Abstract : Introduction. Our objective was to identify mutations in the K-RAS gene in cases of pulmonary metastases from colorectal cancer (CRC) and determine whether their presence was a prognostic factor for survival. Methods. We included all patients with pulmonary metastases from CRC operated on between 1998 and 2010. K-RAS mutations were investigated by direct sequencing of DNA. Differences in survival were explored with the Kaplan-Meier method log-rank tests and multivariate Cox regression analysis. Results. 110 surgical interventions were performed on 90 patients. Factors significantly associated with survival were disease-free interval ( P = 0.002 ), age ( P = 0.007 ), number of metastases ( P = 0.001 ), lymph node involvement ( P = 0.007 ), size of the metastases ( P = 0.013 ), and previous liver metastasis ( P = 0.003 ) . Searching in 79 patients, K-RAS mutations were found in 30 cases. We did not find statistically significant differences in survival ( P = 0.913 ) comparing native and mutated K-RAS. We found a higher rate of lung recurrence ( P = 0.040 ) and shorter time to recurrence ( P = 0.015 ) in patients with K-RAS mutations. Gly12Asp mutation was associated with higher recurrence ( P = 0.022 ) and lower survival ( P = 0.389 ) . Conclusions. The presence of K-RAS mutations in pulmonary metastases does not affect overall survival but is associated with higher rates of pulmonary recurrence.